Analisis Sosiologis Crypto Sebagai Aset Benda Digital Dalam Hukum Perdata - Novandria, Eugene Rangga; Urbanisasi, Urbanisasi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The development of data and communication innovation has encouraged the emergence of untapped developments in the financial world, one of which is cryptocurrency. As a digital asset that uses blockchain innovation, cryptocurrency offers convenience in exchange, but also presents major challenges in terms of direction and legal recognition. This consideration aims to analyze the sociological perspective of cryptocurrency as a digital asset from the perspective of applicable law. With a sociological approach, this consideration analyzes the social and financial impacts caused by the existence of cryptocurrency, as well as how the concepts of ownership, ownership rights, and exchange of rights can be related to this decentralized digital asset. Legally, there has been a discussion about whether cryptocurrency can be categorized as an asset in applicable law, which has so far mostly referred to physical objects. This consideration also highlights the importance of adapting the legal framework to provide guarantees for the rights of people involved in crypto exchanges, as well as the need for clearer controls to direct the exchange and ownership of these digital assets. Therefore, this consideration contributes to a deeper understanding of the role and challenges of cryptocurrency in a respectable legal setting and its influence on social relations in today's society.